The Practice of Post-vaccination COVID-19 Prevention Strategy Among Healthcare Professionals in Felege Hiwot Referral Hospital, Northwest Ethiopia. (December 2022) - Engdaw, Garedew Tadege; Worede, Eshetu Abera; Destaw Bitew, Bikes
Background: Coronavirus Disease 2019 (COVID-19) is an acute respiratory illness first discovered and identified in China. Countries are taking precautions to prevent COVID-19 in accordance with WHO guidelines. Objective: The objective of this study was to assess the practice of the COVID-19 prevention strategy post-vaccination and associated factors among health care professionals in Felege Hiwot Referral Hospital, Bahir Dar, Northwest Ethiopia, in 2021. Methods: An institutional-based cross-sectional study was carried out at Felege Hiwot Referral Hospital, Bahir Dar. Data were entered into Epi-Info software, version 7.1, and exported to SPSS, version 23, for analysis. Descriptive statistics were used to describe the socio-demographic characteristics of the respondents. The crude odds ratio (COR) and the adjusted odds ratio (AOR) with 95% CI were calculated to determine the coefficient of the COVID-19 prevention strategy. Results: In this study, 68.7% (95% CI: 63.7, 73.8) of health care professionals had good practice of the COVID-19 prevention strategy post-vaccination. Sex (AOR: 1.76; 95% CI: 1.08, 2.89), marital status (AOR: 1.75; 95% CI: 1.09, 2.93), and good attitude toward vaccination (AOR: 3.24; 95% CI: 2.13, 5.48) were significantly associated with the practice of COVID-19 prevention strategies post vaccination. Conclusions: The practices of COVID-19 preventive strategies post-vaccination were good among healthcare professionals. Good attitude toward vaccination, sex (male), marital status (married) were factors determining the occurrences of COVID-19 preventive strategies post-vaccination.